2017
DOI: 10.1007/s00787-017-1083-y
|View full text |Cite
|
Sign up to set email alerts
|

Dealing with difference: a scoping review of psychotherapeutic interventions with unaccompanied refugee minors

Abstract: Unaccompanied refugee minors (URMs) are a population at risk for developing mental problems, post-traumatic stress disorder, anxiety, and/or depression. Therapists working with URMs often have to overcome language and cultural barriers, while taking into account these young people's specific needs. A growing literature describes a wide range of interventions designed to reduce psychopathologies and improve well-being. We summarized the different interventions used with URMs to get an overview of techniques use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(58 citation statements)
references
References 45 publications
1
55
0
2
Order By: Relevance
“…The three other studies looked at cognitive behaviour therapy (CBT) for which there is already a large body of work documented for children exposed to violence and war (Morina, Malek, Nickerson, & Bryant, ). The core components of the therapy, that is, recognizing unhelpful cognitions, behaviours, and developing personal coping strategies, are adapted to focus on different presentations amongst the heterogeneous groups of URMs (Demazure, Gaultier, & Pinsault, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The three other studies looked at cognitive behaviour therapy (CBT) for which there is already a large body of work documented for children exposed to violence and war (Morina, Malek, Nickerson, & Bryant, ). The core components of the therapy, that is, recognizing unhelpful cognitions, behaviours, and developing personal coping strategies, are adapted to focus on different presentations amongst the heterogeneous groups of URMs (Demazure, Gaultier, & Pinsault, ).…”
Section: Resultsmentioning
confidence: 99%
“…Social support, whether that be from peers or a parental figures, is a protective factor in the face of adversity and loss (Demazure et al, ). Having foster carers or guardians in certain placements may give the young people opportunities to better confide and express feelings of despair and hopelessness.…”
Section: Discussionmentioning
confidence: 99%
“…In a scoping review of psychotherapeutic interventions with UMs (Demazure, Gaultier & Pinsault, ) found that evidence is still scarce in this group. Only one RCT was identified.…”
Section: Mental Health Interventionsmentioning
confidence: 99%
“…The review of treatment studies for psychiatrically distressed unaccompanied refugee minors is very revealing in demonstrating the dearth of adequate studies with this group [33], although cognitive behavioural approaches with individuals or groups look promising [34] and interventions that give meaning to the events (psychoeducation, rapport building, and use of narratives) could also be effective [35]. The potential for offering the interventions to large groups and ensuring that the unaccompanied minors find them rewarding and effective and can make sense of the interventions is also important [36].…”
Section: Unaccompanied Refugee Minorsmentioning
confidence: 99%